2020
DOI: 10.1021/acs.est.0c06386
|View full text |Cite
|
Sign up to set email alerts
|

Particulate and Dissolved Black Carbon in Coastal China Seas: Spatiotemporal Variations, Dynamics, and Potential Implications

Abstract: Elaborating the spatiotemporal variations and dynamic mechanisms of black carbon (BC) in coastal seas, the geographically pivotal intermediate zones that link the terrestrial and open oceanic ecosystems, will contribute significantly to refine the regional and global BC geochemistry. In this study, we implemented a large spatial-scale and multiseason and -layer seawater sampling campaign in high BC emission influenced coastal China seas (Bohai Sea and Northern Yellow Sea) and quantified the thermal/optical ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 66 publications
4
31
0
Order By: Relevance
“…Coastal seas, including coastal bays, are the geographically critical transitional zone that links terrestrial and open oceanic ecosystems (Bauer et al, 2013;Fang et al, 2018a;Fang et al, 2021). Despite comprising only 7-10% of global ocean surface area, the coastal seas are responsible for 20-30% of global marine primary productivity and up to 80-90% of organic carbon (OC) accumulation in marine sediments (Bauer et al, 2013;Keil, 2017;Fang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Coastal seas, including coastal bays, are the geographically critical transitional zone that links terrestrial and open oceanic ecosystems (Bauer et al, 2013;Fang et al, 2018a;Fang et al, 2021). Despite comprising only 7-10% of global ocean surface area, the coastal seas are responsible for 20-30% of global marine primary productivity and up to 80-90% of organic carbon (OC) accumulation in marine sediments (Bauer et al, 2013;Keil, 2017;Fang et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Soil BC is mobilized to adjacent rivers and then to coastal seas through wind, erosion, and/or leaching pathways (Abney and Berhe, 2018;Coppola et al, 2018), supplying a continuous contribution of fire-derived carbon to the aquatic environments (Wagner et al, 2018). In the natural water bodies, BC occurs simultaneously as particulate and dissolved phases (i.e., PBC and DBC) (Wagner et al, 2015;Wang et al, 2016;Xu et al, 2016;Myers-Pigg et al, 2017;Fang et al, 2018a;Wagner et al, 2018;Qi et al, 2020;Fang et al, 2021;Liu and Han, 2021). Available studies regarding process-based BC fluxes suggested that global rivers deliver 17-37 and 18-66 Tg-C yr −1 of PBC and DBC to the coastal seas, respectively (Jaffé et al, 2013;Coppola et al, 2018;Jones et al, 2020;Fang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations